Identifying and analyzing drivers of innovative behavior based on strategic management of human resources in knowledge-based organizations - Mitra Sadoughi (مدیریت و چشم انداز آموزش)
The purpose of this study aims to identify and analyze innovative behavior proposals based on strategic human resource management in knowledge-based organizations. The research is applicable in terms of purpose, and mixed (qualitative-quantitative) in terms of the type of data. Statistical population in the qualitative sector includes 11 faculty members of Islamic Azad University of Mazandaran Province, and in a targeted sampling; and in quantitative section including 411 managers, consultants, and other faculty active in Islamic Azad University growth and technology centers units of Mazandaran province, selected by the random sampling method. The data collection tool in the qualitative part of the interview was semi-structural interview, and in the quantitative part of the researcher-made questionair. The validity and reliability of the tool in the qualitative sector were approved by the criteria of validity, transmission, and approval; and validity of the tool in the quantitative part was obtained with the opinion of experts and factor analysis, and its reliability with Cronbach's alpha coefficient. Qualitative data analysis was performed by the content analysis, and quantitative data through structural equation analysis. The findings from the qualitative section resulted in the identification of 12 main categories. Also, the findings of data analysis in the quantitative section showed that the extracted pattern has good fit; and behavioral capabilities, performance evaluation, thoughtfulness, job satisfaction, self-efficacy, justice-orientation, participation, competitiveness, professional ethics, Inter-sectoral relationship, collaborative management, and pragmatism, have respectively had the highest importance in developing innovative behaviors in knowledge-based organizations and university development centers. Extended abstract Introduction With the increasing progress of knowledge and technology and the widespread flow of information, our society today needs to nurture human beings who can face and solve problems in a creative way. With this approach, the need for education, reinforcement of creativity, and creating new thoughts to reach the prosperous community is of particular importance (Jahangir et al, 2023). The continuous improvement of organizational performance creates a huge synergy force that can support the growth and development plan, and create organizational excellence opportunities. Governments, organizations, and institutions are trying to do so (Khani Noghani, 2021). One factor effective in improving the process of organizational creativity and individual innovation is the identification of the weakness and strength of the organization is in this section. For this purpose, the periodic evaluations of the organization and management in the field of innovation tasks can be effective (Moussa & El Arbi, 2020). Organizations can increase innovation in different sectors by promoting culture, structures, strategies and processes. The source of innovation in organizations is the creation and enhancement of creativity in the organization (KuideiShat & Farmanesh, 2022). Behavioral innovation is an important and vital factor for organizations to create sustainable competitive value and advantage in today's complex and variable environment. With more innovation, organizations will be more successful in responding to variable environments and developing new capabilities that allow them to get better performance (Vakili et al, 2019). Innovation and innovative measures are largely dependent on the knowledge, expertise and commitment of the employees as the value-creation process inputs. Human resource knowledge and competencies are valuable assets for organizations (Nikkhah Tekmedash et al, 2019). Human resource measures are the main tools and methods that organizations can influence the skills, attitudes, and behavior of individuals to do their work and achieve existing organizational goals (Lancker et al, 2016). In today's competitive world, the only sustainable competitive advantage of any organization is its human resources and the role of all of them in the success of the organization, which is through empowerment, innovative behavior, and creativity of the staff (Sahami, 2020). Today, human resources are considered to be the greatest asset of any organization in terms of thinking ability, creativity and modernization; as any improvement in technical and organizational systems is made by manpower. The intellectual power and thoughts of the staff are static and latant in the organization (Irajirad & Lotfi Khatoonabad, 2019). So, in view of the above, the researcher seeks to answer the question: What is the identification and analysis of strategic human resource management propellers in knowledge -based organizations? Theoretical Framework Innovative behavior: Researchers have agreed that the innovative behavior of employees encompasses employees' creativity, namely the production of new ideas and useful ideas in relation to products, services, processes and procedures; and the more particularly implementation of created ideas. Innovative behavior includes a set of behavior, namely search for opportunities; and producing ideas includes searching and identifying opportunities for innovating and producing ideas and solutions to use opportunities, and also defending produced ideas and the promotion of manufactured ideas aimed at finding support and building cooperation and unity (Sahami, 2020). Strategic Management of Human Resources: The human resources of each organization are the largest and most scientific assets of the organization. Innovation measures are dependent on the knowledge and expertise of employees as the value creation process (Lancker et al, 2016). Human resource measures are the main tools and ways that organizations can influence people's skills, attitudes and behaviors to achieve organizational goals. Human resource has never depreciated by consumption, but the experience and skill it acquires makes organizations perform ore better and more (Vakili et al, 2019). Knowledge-based organization: Knowledge-based organizations are usually described in terms of their product or service knowledge. In other words, the knowledge-based organization is an organization whose products (or services) are knowledge-oriented. The concentration and structure of the knowledge-based organization is a result of organizational learning, and the processes, goals, and generalization of such organizations, which are related to the global perspective and culture, are knowledge-oriented. Structure in knowledge-based organizations includes individuals, processes and information technology (Asgari et al, 2020). Ohadi & Hazraty (2024) examine the impact of cultural diversity on innovative work behavior and psychological adaptation with regard to the role of cultural intelligence. The result of research hypotheses indicates a positive and significant effect of cultural diversity on cultural intelligence as well as the impact of cultural diversity and cultural intelligence on innovative work behavior. The mediating role of cultural intelligence in relation to cultural diversity and innovative work behavior was also confirmed. In addition, the role of cultural intelligence equallizer in relation to cultural diversity and psychological adaptation was also confirmed. Banmairuroy et al, (2022) examined the impact of knowledge-based leadership and human resource development on sustainable competitive advantage through the factors of organizational innovation. Human resource management can help organizational capabilities as far as it creates a set of task behaviors that shape the company identity, innovation, qualitative orientation, and so on. On the other hand, knowledge-based leadership and human resource development have had a positive and constructive impact on the sustainable competitive advantage of companies. Research methodology The research is applicable in terms of purpose, and mixed (qualitative-quantitative) in terms of the type of data. Statistical population in the qualitative sector includes 11 faculty members of Islamic Azad University of Mazandaran Province, and in a targeted sampling; and in quantitative section including 411 managers, consultants, and other faculty active in Islamic Azad University growth and technology centers units of Mazandaran province, selected by the random sampling method. The data collection tool in the qualitative part of the interview was semi-structural interview, and in the quantitative part of the researcher-made questionair. The validity and reliability of the tool in the qualitative sector were approved by the criteria of validity, transmission, and approval; and validity of the tool in the quantitative part was obtained with the opinion of experts and factor analysis, and its reliability with Cronbach's alpha coefficient.